1991
DOI: 10.1148/radiology.178.3.1994406
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of vascular stenosis with color Doppler flow imaging: in vitro investigations.

Abstract: The accuracy of quantifying the degree of vascular stenosis with color Doppler flow imaging (7.5-MHz, linear array system) was determined in an experimental study carried out on six concentric and five eccentric model stenoses (cross-sectional area reduction, 13.4%-93.8%). The measurements were made with use of pulsatile flow at four different flow rates (70.8-339.0 mL/min). The degree of stenosis was calculated from the ratio of prestenotic to intrastenotic flow velocity. The most exact measurement of the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…It is known that increases in intrastenotic velocity may extend a few centimeters beyond anatomic narrowing. 37 We found that if an increased PSV of the C1 existed, a normal C1/ICA index allowed us to exclude all false-positive cases (except 1 complicated case in which there was contralateral MCA occlusion with collateralization by the ACA and bilateral PCA occlusion with collateralization via the ipsilateral MCA branches and ACA). Diagnosing Ն50% stenosis in the C1 segment requires increases in the PSV and the C1/ICA index above an age-dependent mean value Ϯ 2.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is known that increases in intrastenotic velocity may extend a few centimeters beyond anatomic narrowing. 37 We found that if an increased PSV of the C1 existed, a normal C1/ICA index allowed us to exclude all false-positive cases (except 1 complicated case in which there was contralateral MCA occlusion with collateralization by the ACA and bilateral PCA occlusion with collateralization via the ipsilateral MCA branches and ACA). Diagnosing Ն50% stenosis in the C1 segment requires increases in the PSV and the C1/ICA index above an age-dependent mean value Ϯ 2.…”
Section: Discussionmentioning
confidence: 81%
“…22 In a recent study, Lee et al 46 used extracranial ICA flow data for detection of Ͼ50% stenosis of the intracranial ICA, including the MCA, which can also be used for screening patients. 37,38 Despite recent advantages in critical care, neurosurgery, and endovascular therapy, treatment of cerebrovascular disorders remains problematic. Such endovascular techniques as angioplasty and stent placement of symptomatic intracranial stenosis may allow the treatment of previously "untreatable" disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that intrastenotic velocity increase may persist for a few centimeters ("jet") and surpass the anatomic extent of narrowing. 36 The jet is likely to increase the probability of detecting a stenosis and may lead to a more favorable angle of insonation in curved vessels. Nevertheless, TCCS missed 2 Ͻ50% stenoses located in MCAs with downward convex courses at angiography.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proposed algorithms are difficult to implement in clinical situations due to the high computational cost of FEM and the extensive recalculations of the guidewire position. Konings et al [9,10] presented a method in which the guidewire is divided into connected beam elements, and the position of guidewire was expressed as an energy minimization function. The proposed energy function model based on Hooke's law and the theoretical mechanics on bending energy was iteratively minimized.…”
Section: Introductionmentioning
confidence: 99%